Early childhood care and development : some thoughts on how to invest - Myers, Robert G. (IDB WashingtonUS, 1999)
Presents six strategies that can be adopted to improve childhood care and development. Suggests principles or guidelines that should be followed if investments are to have maximum effect. Looks at costs and financing of early childhood care and development programmes.